2011
DOI: 10.1007/s00436-011-2305-8
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil and eosinophil chemotactic factors in the excretory/secretory products of sheep abomasal nematode parasites

Abstract: Both eosinophil chemotactic factor (ECF) and neutrophil chemotactic factor (NCF) activities were demonstrated in excretory/secretory (ES) products and homogenates of Haemonchus contortus and Teladorsagia circumcincta larvae and adult worms in a modified checkerboard assay using a micro-chemotaxis chamber. Neutrophil chemotaxis was seen in 28 of 35 experiments and eosinophil chemotaxis in 20 of 38 experiments. Chemokinetic activity for neutrophils and eosinophils (accounting for 40-50% of total cell migration) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…Inside the host, H. contortus secrete and excrete various proteins that mediate modulatory or suppressive potential for immune responses during host parasite interactions. These responses are governed by the interaction of these proteins through receptor-ligand systems on the surface of host cells [30,38]. In our recent study, H. contortus tropomyosin was identified in excretory and secretory (ES) protein to bind to goat PBMCs in vivo at a specific developmental stage (L4 + L5) of the parasite [20], however, the host cells-related immunoregulatory functions affected by Hc-TpMy were not highlighted yet.…”
Section: Discussionmentioning
confidence: 97%
“…Inside the host, H. contortus secrete and excrete various proteins that mediate modulatory or suppressive potential for immune responses during host parasite interactions. These responses are governed by the interaction of these proteins through receptor-ligand systems on the surface of host cells [30,38]. In our recent study, H. contortus tropomyosin was identified in excretory and secretory (ES) protein to bind to goat PBMCs in vivo at a specific developmental stage (L4 + L5) of the parasite [20], however, the host cells-related immunoregulatory functions affected by Hc-TpMy were not highlighted yet.…”
Section: Discussionmentioning
confidence: 97%
“…The scientific literature is replete with examples of helminth-derived excretory/secretory products, extracts or semi-purified molecules directly affecting a variety of functions of innate immune cells [25,26]. Indeed, products from nematode and trematode parasites can be chemoattractants for neutrophils in vitro [27][28][29]: thus, it was unexpected when HdE failed to elicit neutrophil chemotaxis in under-agarose or transwell systems. Contrari- NØs) migration towards WKYMVm (1 μM) in a transwell assay (8 μm pore size filter) is unaffected by a 30 min pre-treatment with LPS (1 μg/mL) or the calcium ionophore, A23187 (2.5 μM).…”
Section: Discussionmentioning
confidence: 99%
“…The suppression of neutrophil chemotaxis is intriguing, particularly since other reports on helminth-derived molecules describe them as neutrophil chemoattractants [27][28][29][30]. Schroeder et al reported that live microfilariae of Brugia malayi blocked transendothelial migration of neutrophils but did not determine if this was via the release of a molecule from the nematode [31].…”
Section: Doi: 101159/000492303mentioning
confidence: 99%
“…After larvae activate complement, vasoactive and chemotactic peptides (C3a and C5a) are generated, and these peptides mobilize eosinophils to the area of infection independently of specific mechanisms (CD4+ and IL-5). At the same time, H. contortus secretes chemoattractants for eosinophils and neutrophils, which reinforce the inflammatory response [57]. The thymus-independent increase in tissue eosinophils is an important innate response in which complement activation mediates the cytotoxicity of eosinophils against larvae in early infection stages in the absence of specific antibodies.…”
Section: Immune Response In Ovine Haemonchosismentioning
confidence: 99%